O estado do conhecimento sobre a relação da Olimpíada Brasileira de Matemática das Escolas Públicas (OBMEP) com o ensino de Matemática nas teses e dissertações no período de 2008 a 2021 - Borges, Fábio de Sá (2022)
The present study aims to analyze the productions of master's and doctoral degrees, accomplished between 2008 and 2021, that presented investigations related to the importance of the Brazilian Public Schools Mathematics Olympics (OBMEP) in the teaching of Mathematics. It is a bibliographic research of qualitative approach with exploratory character, in the State of Knowledge type. The research was developed from a collection from the catalogs of the Bank of Theses and Dissertations of CAPES and the Brazilian Digital Library of Theses and Dissertations, both available on electronic platforms, culminating in a selection of five theses and 135 dissertations. A reading form was used as an instrument to record the references of the analyzed studies. The systematic study of the general characteristics of the research was developed based on seven categories, established a posteriori: C1 – Teaching proposal with OBMEP as a complement; C2 – Problem Solving Methodology applied to OBMEP questions; C3 – Analysis of results and performances; C4 – Critical analysis of questions; C5 – Analysis of errors as methodology in the analysis of answers; C6 – Relation to theoretical, educational, philosophical and political aspects; and C7 – Research with more diverse themes, with OBMEP in a secondary role. Among the results, it was verified that most of the productions are concentrated in the Professional Master in Mathematics in National Network (PROFMAT) Program, prevailing works focused on the presentation of didactic-methodological teaching strategies, typical of professional masters. In addition, in most studies, there is a predominance of the contributions of OBMEP and its programs and portals in the field of mathematics teaching. However, there is a lack of investigations that have OBMEP as the main object, or research with deeper reflections on the impacts of OBMEP on the teaching and learning Mathematics process, especially regarding the goal of social inclusion of the Olympics.